Neoliberal populism and the "Özal decade": its implications for the democratic process - Tafolar, Mine. (Thesis (M.A.)-Bogazici University. Institute Ataturk of Modern Turkish History, 2008., 2008)
This study examines the Özal decade through the lens of populism and scrutinizes the manifestations of this neoliberal populist governance style on the economic, discursive, and institutional levels in a detailed manner. Throughout these analyses, the study contextualizes the neopopulist manifestations of the period within the general framework of Turkey’s overall experiment with populism. In addition to comparing and contrasting Özal’s neopopulist governance style with that of his populist predecessors and demarcating its parallels and distinctions from the characteristics of populism carried out in the previous periods in the Turkish context, it situates Özal’s governance practice within a broader and worldwide framework through the analysis of manifestations of neoliberal populism in Latin America. This analysis reveals that Turkey is a typical case study with its neopopulist governance practices. Within the framework of the detailed search of the fundamental manifestations of Özal’s neopopulist governance style at different levels, it is argued that this governance style had adverse implications for the quality of democracy in Turkey and undermined the basic credentials of democracy which needed to be based on the empowerment of individuals, the notion of citizenship, and the participatory roles attributed to intermediary institutions and civil society organizations. The period is evaluated as a case in point in which the “man of the people” turned into an authoritarian leader who governed the country in an extensively top-down and arbitrary manner.
Keywords: Populism -- Turkey.